Starch-type combined slurry for low-dielectric glass fiber electronic yarn and sizing process of starch-type combined slurry

By using starch-type combined slurry, especially the coordinated combination of cationic denatured starch and oxidized esterified double-denatured starch, the problem of low mechanical and electrical properties of low dielectric glass fiber electronic yarns is solved, and the efficiency of slurry is achieved The quality of the fabric is stable.

CN119465637APending Publication Date: 2025-02-18OCEAN UNIV OF CHINA

Patent Information

Application Number
CN202411597177.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Because the glass contains more boron oxides, the low-dielectric fiberglass electronic yarn has low mechanical and electrical properties, and the simmering time is prolonged, and the surface organic matter residue increases, affecting product quality.

Method used

The starch-type combined slurry is made of cationic denatured starch, oxidized esterified double-denatured starch, partially alcoholized polyvinyl alcohol and polyethylene glycol, and the adhesion, flexibility and heat of the slurry are improved through synergistic combination. stability.

Benefits of technology

It improves the mechanical and electrical properties of low-dielectric glass fiber electronic yarn, shortens the simmering time, reduces the surface organic matter residues, and ensures the quality stability of the fabric.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465637A_ABST
    Figure CN119465637A_ABST
Patent Text Reader

Abstract

The invention discloses starch type combined slurry for low-dielectric glass fiber electronic yarn and a sizing process of the starch type combined slurry. The combined slurry is prepared from a starch compound, partially alcoholyzed polyvinyl alcohol, polyethylene glycol and water according to the weight ratio of (1.4-1.6): 1: 1. The starch compound is composed of cationic composite modified starch and oxidized and esterified dual-modified starch which are equal in weight; the cationic modified starch is prepared by modifying natural starch by using cationic epoxide as a modifier; the oxidized and esterified dual-modified starch is prepared by modifying natural starch by taking hydrogen peroxide as an oxidizing agent and acetic anhydride as an esterifying agent; the combined sizing agent not only effectively improves the mechanical performance of the TLD glass fiber electronic yarn, improves the flexibility of a sizing film and avoids damage and falling caused by friction in weaving, but also ensures the sizing quality, reduces the sizing cost and the combustible content on the surface of the electronic yarn, shortens the smoldering time, and maximally retains the mechanical strength of the fabric.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glass fiber yarn weaving, in particular to a starch type combined sizing material for low-dielectric glass fiber electronic yarn and a sizing process thereof. Background Art

[0002] Glass fiber electronic yarn (abbreviated as glass fiber electronic yarn) needs to be sized before weaving to improve the mechanical properties and wear resistance of the glass fiber yarn and reduce the hairiness, so as to ensure the smooth progress of the subsequent weaving steps and ensure product quality; then, the glass fiber electronic yarn fabric made by weaving needs to go through the desizing step to remove the surface sizing, so as to ensure the smooth progress of the subsequent finishing and other series of processes.

[0003] Different from other types of textile materials, glass fiber electronic yarn, as an inorganic mineral material, has a certain heat resistance, so it is usually processed by high-temperature simmering, that is, the grey cloth is thermally desized at a temperature of ≥400°C; in the thermal desizing process, the temperature and time settings are the key factors that determine the quality of glass fiber electronic yarn fabrics; when the simmering time is insufficient, the slurry on the surface of the glass fiber electronic yarn is not completely removed, affecting the subsequent finishing process and the electrical properties of the product, and when the simmering time is too long, it will cause irreversible structural damage to the fibers in the glass fiber electronic yarn, resulting in a decrease in the mechanical properties of the yarn and fabric.

[0004] Among the various types of glass fiber electronic yarns, low dielectric glass fiber electronic yarn (abbreviated as TLD glass fiber electronic yarn) contains more boron oxides inside the glass body; on the one hand, the presence of boron oxides increases the phase separation of the glass, reduces the strength of the fiber, and makes the mechanical properties of TLD glass fiber electronic yarn and its fabric generally lower than other types of glass yarn and fabric; on the other hand, the boron oxides in the glass body precipitate from the glass body after sintering and migrate to the surface of the yarn, which has a flame retardant effect on the surface sizing, resulting in a prolonged sintering time. At the same time, the organic matter residue on the surface of the yarn and fabric after sintering increases, further reducing the mechanical and electrical properties of TLD glass fiber electronic yarn and its fabric. Therefore, for low dielectric glass fiber electronic yarn, the selection of sizing agent in the sizing step is crucial; the sizing component must not only have good viscosity, film-forming and protective properties with the TLD glass fiber electronic yarn, so as to facilitate the smooth progress of the weaving process; and the thermal stability of the sizing component should not be too high to ensure the smooth progress of the subsequent thermal desizing process and ensure the stability of various properties and quality of the fabric. Therefore, the current common glass fiber yarn sizing formula is not suitable for the weaving of TLD glass fiber electronic yarn. It is necessary to develop a low dielectric glass fiber electronic yarn sizing sizing according to the chemical composition characteristics of TLD glass fiber electronic yarn containing boron oxide. Summary of the invention

[0005] The object of the present invention is to provide a starch-based composite slurry which can solve the above-mentioned technical problems and is suitable for use in low-dielectric glass fiber electronic yarn.

[0006] Another object of the present invention is to provide a method for preparing the above-mentioned starch-based composite slurry for low-dielectric glass fiber electronic yarn.

[0007] Another object of the present invention is to provide a sizing process based on the cationic-oxidized esterified starch composite slurry for low dielectric glass fiber electronic yarn.

[0008] To this end, the technical solution of the present invention is as follows:

[0009] A starch-based composite slurry for low-dielectric glass fiber electronic yarn is composed of a starch composite, partially alcoholyzed polyvinyl alcohol, polyethylene glycol and water; wherein the starch composite is composed of equal weights of cationic modified starch and oxidized esterified double modified starch; and the weight ratio of the starch composite, partially alcoholyzed polyvinyl alcohol and polyethylene glycol is (1.4-1.6):1:1.

[0010] In the slurry, the cationic modified starch is an etherified derivative cationic modified starch prepared by using natural starch as raw material and a cationic modifier, and has the following chemical structure:

[0011]

[0012] Wherein, n is 600~800.

[0013] Since the cationic modified starch carries positive ion groups on its molecular chain (specifically, the nitrogen atom carries a positive charge), it can be strongly adsorbed and coordinated with the negatively charged glass fiber as one of the components of the slurry, which not only has the effect of eliminating static electricity, but also can improve the bundling of the fibers, so that the glass fiber yarn has higher wear resistance, modifiability and bendability, and can further enhance the adhesion of the slurry to the glass fiber, improve the strength of the bonding layer between the fibers, so as to further improve the strength of the yarn, and make up for the problem of low strength of the low dielectric glass yarn due to the high boron content to the greatest extent.

[0014] Specifically, the cationic modified starch is prepared by using cationic epoxide as a modifier to modify natural starch by a water phase nucleophilic substitution method. The chemical structure of the cationic modified starch is:

[0015]

[0016] In the slurry, the oxidized esterified double-modified starch uses natural starch as a raw material, acetic anhydride as an esterifying agent, and uses an oxidant to adjust its viscosity, thereby preparing a composite modified starch having the following chemical structure:

[0017]

[0018] In the formula, o is 300~400, and p is 300~400.

[0019] The oxidized esterified double-modified starch has a low viscosity characteristic, specifically 9cp-10cp, which makes it have good permeability to glass fiber filament yarn; at the same time, due to its low film glass transition temperature, it has high strength and flexibility, can improve the wear resistance of the sizing yarn, reduce the sizing yarn falling during weaving, so the weaving performance is good; the introduction of esterified groups can significantly reduce the glass transition temperature of the starch film, improve the flexibility of the sizing yarn, reduce the shedding of the film, the introduction of oxygen-containing groups can enhance the hydrogen bonding force between the starch film and the glass fiber, improve the adhesion of the sizing to the glass fiber yarn, and improve the mechanical strength of the sizing yarn; in addition, by reducing the degree of polymerization of the starch main chain and introducing carboxyl and aldehyde groups into the starch macromolecules, the solubility of the starch sizing is increased, the gelatinization temperature is reduced, the viscosity is reduced, the fluidity of the starch sizing is increased, and the permeability to the glass fiber yarn is increased, so as to form a firm bonding layer between the glass fibers inside the yarn body, thereby improving the strength of the TLD yarn.

[0020] Specifically, the oxidative esterified double-modified starch is prepared by modifying natural starch by a water phase nucleophilic substitution method using inorganic peroxide hydrogen peroxide as an oxidant and acetic anhydride as an esterifying agent.

[0021] The partially hydrolyzed polyvinyl alcohol is a polyvinyl alcohol with a degree of hydrolysis of 87% to 89%, such as polyvinyl alcohol PVA0588. As a water-soluble polymer, the partially hydrolyzed polyvinyl alcohol has good film-forming properties, so it acts as a film-forming agent in the combined slurry; in addition, the partially hydrolyzed polyvinyl alcohol has a lower glass transition temperature, and its slurry film is more flexible and elastic than starch slurry, and has good anti-buckling performance, which can ensure that the sizing yarn is not easy to fall off due to external effects such as stretching, bending and friction during the high-speed movement of the air-jet loom; however, since the partially hydrolyzed polyvinyl alcohol is a carbon chain polymer, its main chain is a CC structure, and its heat resistance is relatively high, its excessive content will lead to a prolonged thermal desizing time of the slurry, and an increase in the amount of organic matter remaining on the surface after simmering, which affects the mechanical properties and surface electrical properties of the final product of the low-dielectric glass fiber electronic cloth. Therefore, under the premise of ensuring the performance of the sizing yarn and the slurry film, the partially hydrolyzed polyvinyl alcohol needs to be compounded with the starch complex in a certain proportion to effectively avoid its above-mentioned characteristics.

[0022] The polyethylene glycol is polyethylene glycol-4000 (PEG-4000). Although polyethylene glycol does not have film-forming properties, it can act as a stabilizer, dispersant and plasticizer in the slurry, so that adding it to the slurry can increase the dispersion of PVA in the slurry, reduce the degree of phase separation of the slurry, and improve the flexibility of the slurry film; in addition, since the polymerization degree of polyethylene glycol is relatively low, it also has the effect of increasing the thermal decomposition rate of the slurry, thereby shortening the simmering time required for subsequent desizing.

[0023] In the composite slurry, pure water is preferably used, and the amount of water used is: the solid content of the cationic modified starch, oxidized esterified double modified starch, partially alcoholyzed polyvinyl alcohol and polyethylene glycol is 9.5wt.% to 10.5wt.%, and the solid content is preferably 10%.

[0024] A method for preparing a starch-based composite slurry for low-dielectric glass fiber electronic yarn comprises the following steps: taking 57.5% to 62.5% of water by total weight; adding polyethylene glycol to the water under stirring and stirring to dissolve; then sequentially adding partially alcoholyzed polyvinyl alcohol, cationic modified starch and oxidized esterified double modified starch, and after the addition is completed, continuing to stir for 5 minutes to obtain a mixed solution; heating the mixed solution to 93.5°C to 96.5°C and keeping the temperature for 30 minutes to ensure uniform gelatinization; finally, adding the remaining pure water to the gelatinized solution and cooling it to 60°C to obtain a composite slurry.

[0025] A sizing process using a starch-based composite sizing agent for low-dielectric glass fiber electronic yarn comprises the following steps: sizing the low-dielectric glass fiber electronic yarn with a composite sizing agent in a single yarn sizing machine; the sizing tank temperature is 58°C to 62°C, the sizing speed is 48.5m / min to 51.5m / min, the sizing force is 0.45KN to 0.55KN, double dipping and double rolling are performed, and the drying room temperature is 77°C to 83°C.

[0026] Compared with the prior art, the starch-based composite slurry for low-dielectric glass fiber electronic yarn is prepared by using cationic modified starch and oxidized esterified starch with synergistic compounding effect, and is matched with polyvinyl alcohol and polyethylene glycol. The synergistic compounding application of cationic modified starch and oxidized esterified starch effectively improves the mechanical properties of TLD glass fiber electronic yarn, while improving the flexibility of the slurry film, and avoiding the damage and shedding of the slurry film due to friction during the weaving process; at the same time, by limiting the proportion of cationic modified starch and oxidized esterified starch in the slurry, the composite slurry can not only ensure the quality of the sizing yarn while reducing the sizing yarn cost, but also reduce the content of combustible matter on the surface of the low-dielectric glass fiber electronic yarn, shorten the smoldering time, and retain the mechanical strength of the fabric to the greatest extent. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The contact angle test results of different slurry formulations of Example 2 of the present invention and Comparative Examples 2 to 5 on a sizing agent film are shown;

[0028] Figure 2 The test graphs of turbidity and anti-coagulation properties of different slurry formulations prepared in Examples 1 to 5 of the present invention after static aging for 1 to 5 hours at 60° C.;

[0029] Figure 3These are electron microscope images of the composite slurry of Example 2 of the present invention initially coated on the low dielectric glass fiber yarn and the yarn in the thermal desizing state after simmering for 12 hours. DETAILED DESCRIPTION

[0030] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments, but the following embodiments are by no means intended to limit the present invention in any way.

[0031] Example 1

[0032] A cationic-oxidized esterified starch composite slurry comprises, by weight, 10.8 parts of cationic modified starch, 10.8 parts of oxidized esterified double modified starch, 14.2 parts of polyvinyl alcohol with an alcoholysis degree of 88%, 14.2 parts of PEG-4000 and 476.3 parts of pure water.

[0033] The composite slurry is prepared by the following steps: taking 60% of the total weight of water; adding PEG-4000 to the water under stirring and stirring to dissolve; then adding part of the alcoholysed polyvinyl alcohol, cationic modified starch and oxidized esterified double modified starch in sequence, and after the addition is completed, continuing to stir for 5 minutes to obtain a mixed solution; heating the mixed solution to 95°C and keeping it warm for 30 minutes to ensure uniform gelatinization; finally, adding the remaining pure water to the gelatinized solution and cooling it to 60°C to obtain a composite slurry.

[0034] Example 2

[0035] A cationic-oxidized esterified starch composite slurry comprises, by weight, 10.8 parts of cationic modified starch, 10.8 parts of oxidized esterified double modified starch, 14.2 parts of polyvinyl alcohol with an alcoholysis degree of 88%, 14.2 parts of PEG-4000 and 450 parts of pure water; the steps for preparing the composite slurry are the same as those in Example 1.

[0036] Example 3

[0037] A cationic-oxidized esterified starch composite slurry comprises, by weight, 10 parts of cationic modified starch, 10 parts of oxidized esterified double modified starch, 14.2 parts of polyvinyl alcohol with an alcoholysis degree of 89%, 14.2 parts of PEG-4000 and 412 parts of pure water; the steps for preparing the composite slurry are the same as those in Example 1.

[0038] Example 4

[0039] A cationic-oxidized esterified starch composite slurry comprises, by weight, 11.3 parts of cationic modified starch, 11.3 parts of double modified starch, 14.2 parts of polyvinyl alcohol with an alcoholysis degree of 87%, 14.2 parts of polyPEG-4000 and 450 parts of pure water; the steps for preparing the composite slurry are the same as those in Example 1.

[0040] Comparative Example 1

[0041] The invention discloses an oxidized esterified double-modified starch composite slurry, which comprises, by weight, 21.6 parts of oxidized esterified double-modified starch, 14.2 parts of polyvinyl alcohol with an alcoholysis degree of 88%, 14.2 parts of PEG-4000 and 450 parts of pure water.

[0042] The composite slurry is prepared by the following steps: taking 60% of the total weight of water; adding PEG-4000 to the water under stirring and stirring to dissolve; then adding part of the alcoholysed polyvinyl alcohol and the oxidized esterified double-modified starch in sequence, and after the addition is completed, continuing to stir for 5 minutes to obtain a mixed solution; heating the mixed solution to 95°C and keeping it warm for 30 minutes to ensure uniform gelatinization; adding the remaining pure water to the gelatinized solution, and cooling it to 60°C to obtain a composite slurry.

[0043] Comparative Example 2

[0044] A cationic-oxidized esterified starch composite slurry comprises, by weight, 15 parts of cationic modified starch, 15 parts of oxidized esterified double modified starch, 10 parts of polyvinyl alcohol with an alcoholysis degree of 88%, 10 parts of PEG-4000 and 450 parts of pure water; the steps for preparing the composite slurry are the same as those in Example 1.

[0045] Comparative Example 3

[0046] A cationic-oxidized starch esterified powder composite slurry comprises, by weight, 12.5 parts of cationic modified starch, 12.5 parts of oxidized esterified double modified starch, 12.5 parts of polyvinyl alcohol with an alcoholysis degree of 88%, 12.5 parts of PEG-4000 and 450 parts of pure water; the preparation steps of the composite slurry are the same as those in Example 1.

[0047] Comparative Example 4

[0048] A cationic-oxidized esterified starch composite slurry comprises, by weight, 8.4 parts of cationic modified starch, 8.4 parts of oxidized esterified double modified starch, 16.6 parts of polyvinyl alcohol with an alcoholysis degree of 88%, 16.6 parts of PEG-4000 and 450 parts of pure water; the steps for preparing the composite slurry are the same as those in Example 1.

[0049] Comparative Example 5

[0050] A cationic-oxidized esterified starch composite slurry comprises, by weight, 5 parts of cationic modified starch, 5 parts of oxidized esterified double modified starch, 20 parts of polyvinyl alcohol with an alcoholysis degree of 88%, 20 parts of PEG-4000 and 450 parts of pure water; the steps for preparing the composite slurry are the same as those in Example 1.

[0051] Comparative Example 6

[0052] A cationic modified starch composite slurry comprises, by weight, 21.6 parts of cationic modified starch, 14.2 parts of polyvinyl alcohol with an alcoholysis degree of 88%, 14.2 parts of PEG-4000 and 352.8 parts of pure water.

[0053] The composite slurry is prepared by the following steps: taking 60% of the total weight of water; adding PEG-4000 to the water under stirring and stirring to dissolve; then adding part of the alcoholysated polyvinyl alcohol and the cationic modified starch in sequence, and after the addition is completed, continuing to stir for 5 minutes to obtain a mixed solution; heating the mixed solution to 95°C and keeping it warm for 30 minutes to ensure uniform gelatinization; adding the remaining pure water to the gelatinized solution, and cooling it to 60°C to obtain a composite slurry.

[0054] Comparative Example 7

[0055] An oxidized starch composite slurry comprises, by weight, 21.6 parts of oxidized starch, 14.2 parts of polyvinyl alcohol with an alcoholysis degree of 88%, 14.2 parts of PEG-4000 and 450 parts of pure water; the preparation steps of the composite slurry are the same as those of comparative example 1.

[0056] In the above embodiments and comparative examples, partially alcoholyzed polyvinyl alcohol, polyethylene glycol, and oxidized starch are directly purchased from commercial products, and cationic modified starch and oxidized esterified double modified starch are prepared by the laboratory; wherein, the cationic modified starch is prepared by modifying natural starch by a water phase nucleophilic substitution method using cationic epoxide as a modifier, the cationic epoxide is shown in the following formula II, and the cationic modified starch is shown in the following formula I; the oxidized esterified double modified starch is prepared by modifying natural starch by a water phase nucleophilic substitution method using hydrogen peroxide as an oxidant and acetic anhydride as an esterifying agent, the oxidized esterified double modified starch is shown in the following formula III;

[0057] Formula I:

[0058] n is 600 to 800;

[0059] Formula II:

[0060]

[0061] Formula III:

[0062] o is 300~400, and p is 300~400.

[0063] Performance Test:

[0064] In order to test the slurry properties, the slurries of Examples 1 to 4 and Comparative Examples 1 to 7 were used to carry out sizing, weaving, desizing, finishing and other treatment processes on low dielectric glass fiber electronic yarns in the same manner.

[0065] The sizing steps are as follows: in a single yarn sizing machine, the composite sizing material is used to size the low dielectric glass fiber electronic yarn; wherein, the sizing tank temperature is 60°C, the sizing speed is 50m / min, the rolling force is 0.5KN, double dipping and double rolling, and the drying room temperature is 80°C.

[0066] (I) Comparative test of yarn properties after sizing with different component size formulas:

[0067] The yarn properties of the composite sizing materials of Examples 1 to 4 and Comparative Examples 1 to 7 after sizing were tested, and the yarn properties tests included breaking strength test, breaking elongation test, stiffness test and flexural strength retention test. The specific test results are shown in Table 1 below.

[0068] Table 1:

[0069]

[0070] From Table 1, we can see that

[0071] (1) Analysis of Examples 1 to 4:

[0072] After the low dielectric glass fiber electronic yarn is sized by the cationic-oxidized esterified starch composite slurry prepared in Examples 1 to 4, that is, by controlling the weight ratio of the starch composite, partially alcoholyzed polyvinyl alcohol and polyethylene glycol in the slurry formula to be (1.4-1.6):1:1, and the compounding ratio of the cationic modified starch and the oxidized esterified double modified starch in the starch composite to be 1:1, the sizing breaking strength is maintained at 0.63N / tex-0.67N / tex, the breaking elongation is maintained at 3.33%-3.46%, the stiffness is 91.9mm-92.8mm, and the flexural strength retention rate is 65.9%-68.3%, indicating that the combined slurry has a stable enhancing effect on the mechanical properties of the glass fiber yarn and has good reproducibility in the process;

[0073] (2) Analysis of Example 2, Comparative Example 1 and Comparative Example 7:

[0074] Comparative Example 1 prepared an oxidized esterified double-modified starch composite slurry, which differs from the cationic-oxidized esterified starch composite slurry prepared in Example 2 in that no cationic modified starch is added; from the comparison of the test results of the two in Table 1, it can be seen that the performance of the product obtained by sizing the low dielectric glass fiber electronic yarn with the composite slurry of Comparative Example 1 in four aspects, namely, breaking strength, breaking elongation, stiffness and flexural strength retention rate, is significantly lower than the treatment effect of the composite slurry of Example 2 on the low dielectric glass fiber electronic yarn; specifically, the breaking strength of the product obtained by using the slurry of Example 2 is increased from 0.62N / tex to 0.65N / tex, the breaking elongation is increased from 3.23% to 3.42%, the stiffness is reduced from 97.3mm to 92.0mm, and the flexural strength retention rate is increased from 59.5% to 67.1%.

[0075] Comparative Example 7 prepared an oxidized starch composite slurry, which is different from the oxidized esterified double-modified starch composite slurry prepared in Comparative Example 1 in that the ordinary oxidized starch mentioned in the background technology is used instead of the oxidized esterified double-modified starch; from the comparison of the test results of the two in Table 1, it can be seen that the product obtained by sizing the low dielectric glass fiber electronic yarn with the slurry of Comparative Example 7 has a similar treatment effect on stiffness, but its breaking strength, elongation at break and flexural strength retention rate are all lower than those of Comparative Example 1, that is, the treatment effect is worse than that of Comparative Example 1.

[0076] The analysis of the performance differences between the above-mentioned Example 2, Comparative Example 1 and Comparative Example 7 is as follows:

[0077] First, in the conventional sizing slurry (Comparative Example 7) and the slurry using only oxidized esterified double-modified starch (Comparative Example 1), polyvinyl alcohol and oxidized starch have more acidic groups in their macromolecular main chains, such as hydroxyl and carboxyl groups, which are easily negatively charged after dissociation, and have a certain electrostatic repulsion with the negatively charged silanol hydroxyl Si-OH on the surface of the glass fiber, resulting in weak adhesion between the slurry and the glass fiber, which is not conducive to the improvement of the mechanical strength of the glass fiber electronic yarn; while the slurry formula of Example 2 is added with cationic modified starch, which has positively charged groups on its macromolecular main chain, and can form electrostatic force with the negatively charged glass fiber surface, thereby enhancing the adhesion between the slurry and the yarn, improving the firmness of the bonding layer, and improving the breaking strength of the low dielectric glass fiber electronic yarn.

[0078] Second, the glass fiber in the low-dielectric glass fiber electronic yarn is an inorganic mineral material with high modulus and very low elasticity. Therefore, the elongation at break of the glass fiber yarn is lower than that of other types of yarn materials. The poor flexibility of the size film and the bonding layer on the yarn surface leads to a further decrease in the elongation at break of the glass fiber yarn. The slurry formula of Example 2 improves the elongation at break of the low-dielectric glass fiber electronic yarn by introducing cationic modified starch, while reducing the stiffness. This is because the 2-hydroxy-propyltrimethylammonium chloride substituent group in the cationic modified starch has a longer molecular chain, which plays an internal plasticizing role, thereby improving the flexibility of the main chain of the slurry macromolecule, improving the elasticity and softness of the size film to a certain extent, improving the flexibility and wear resistance of the slurry yarn, and improving the protectiveness of the slurry to the yarn body.

[0079] Third, during the weaving process, the glass fiber yarn is not only subjected to stretching and friction, but also to repeated bending fatigue stress; this fatigue stress is mainly caused by the repeated opening movement of the warp yarn in the weaving area, and the repeated friction with the heald, that is, the adjacent warp yarn; therefore, the bending resistance of the glass fiber yarn depends to a large extent on the flexibility of the sizing film and the sizing yarn, and affects the weaving efficiency and product performance. The bending resistance is mainly measured by rubbing the yarn at a certain angle on a cohesive force testing machine for a certain number of times under pre-tension, and then measuring the breaking strength, and comparing it with the unrubbed yarn, and expressing it as the breaking strength retention rate; the sizing effect of the sizing agent in Example 2 is significantly improved compared with that in Comparative Example 1, which is also caused by the internal plasticization of the cationic modified starch. By improving the flexibility and toughness of the sizing film, it is less likely to be damaged and fall off when subjected to periodic stretching and friction, thereby improving the protectiveness of the low-dielectric glass fiber electronic yarn.

[0080] In summary, the introduction of cationic modified starch in the slurry formula significantly improves the sizing performance of low dielectric glass fiber electronic yarn, and the yarn breaking strength, elongation at break, softness and flex resistance are significantly improved compared with before the introduction. This is mainly because the cationic modified starch can improve the adhesion of the slurry to the glass fiber through electrostatic force, and at the same time, it utilizes the flexibility of its main chain to improve the elasticity and flexibility of the slurry film and the slurry bonding layer through internal plasticization, which is also one of the important innovations of the present invention.

[0081] (3) Analysis of Example 2 and Comparative Example 6:

[0082] Comparative Example 6 prepares a cationic modified starch composite slurry, which differs from the cationic-oxidative esterified starch composite slurry prepared in Example 2 in that no oxidative esterified double modified starch is added; from the comparison of the test results of the two in Table 1, it can be seen that the product obtained by sizing the low dielectric glass fiber electronic yarn with the composite slurry of Comparative Example 6 is not only higher in stiffness than the treatment effect of Example 2 (the weavability of the glass fiber yarn decreases with increasing stiffness), but also lower in breaking strength, breaking elongation, and flexural strength retention rate than the treatment effect of Example 2, and the treatment effect is worse than that of Comparative Example 1. It can be seen that whether cationic modified starch is used alone or oxidative esterified double modified starch is used alone, the treatment effect of the low dielectric glass fiber electronic yarn will be poor, that is, the synergistic compounding effect of cationic modified starch and oxidative esterified double modified starch is required to improve the two.

[0083] The plasticizing effect of a single cationic modified starch on starch film is limited, and the adhesion to glass fiber is mainly through electrostatic force, resulting in a relatively single force; the present application uses a compound of cationic modified starch and oxidized esterified double modified starch containing non-polar groups (specifically acetyl groups), which not only reduces the polarity of starch macromolecules in the film and increases the plasticity of the film, but also, on the other hand, the more oxygen-containing groups in the oxidized esterified double modified starch can form hydrogen bonds with glass fibers, thereby enhancing the strength and type of the force between the film and the fiber. Therefore, compared with the slurry formula using a single type of starch, the present application uses a synergistic compound of cationic modified starch and oxidized esterified double modified starch to further improve the sizing performance, that is, the yarn breaking strength, elongation at break, softness and flex resistance are all improved, which is another important innovation of the present invention.

[0084] (II) Slurry properties of different component slurry formulas:

[0085] In view of the requirements of glass fiber yarn for sizing during the sizing process, the surface tension, viscosity, contact angle and aging performance of the cationic-oxidized esterified starch composite sizing prepared in Example 2 and Comparative Examples 2 to 5 were tested in turn. The specific test results are shown in Table 2 below.

[0086] Table 2:

[0087]

[0088] The analysis based on the performance test results in Table 2 is as follows:

[0089] (1) Surface tension and viscosity of slurry: Surface tension determines the wetting and spreading performance of slurry on the surface of glass fiber yarn, and is a necessary prerequisite for forming a good film and adhesion on glass fiber yarn. This is mainly affected by the fluidity and cohesion of slurry. The molecular weight of starch complex is much higher than that of polyvinyl alcohol and polyethylene glycol, and has a branched structure. Therefore, as shown in Table 2, as the proportion of starch complex in slurry increases, the flow resistance of slurry increases, and the corresponding surface tension tends to increase. Secondly, cationic modified starch carries a positive charge and has a strong interaction with the electronegative groups on the molecular structure of other components of slurry. When the proportion of starch complex increases, the cohesion between slurry molecules increases, which also causes the surface tension of slurry to increase.

[0090] The viscosity change trend of the slurry in Table 2 is consistent with the change trend of the surface tension, that is, as the proportion of starch complex increases, the viscosity also tends to increase, which is also caused by the increase in the cohesive force between the slurry molecules; and if the viscosity and surface tension of the slurry are too high, it will inevitably lead to its weakened wetting and spreading ability on the glass fiber surface, thereby reducing the penetration rate, and the sizing result is mainly covering, which not only leads to less slurry inside the yarn and weaker bonding between fibers, but also causes the slurry layer to be too thick, and the flexibility and flexure of the slurry film are reduced, which is easy to cause damage and falling off; if the viscosity is too low, the adhesion of the slurry is reduced, the sizing rate is reduced, and the mechanical properties of the sizing yarn are reduced; this is consistent with the test results in Table 1 above.

[0091] (2) Wetting properties of slurry: Rapid and effective wetting is a necessary prerequisite for the slurry to form good adhesion to the glass fiber yarn. The contact angle is affected by the surface energy and fluidity of the slurry, and is an intuitive reflection of the slurry's wetting properties and bonding rate on the glass fiber yarn surface. Specifically, in the production process of glass fiber electronic yarn, the glass fiber yarn needs to be coated with a wetting agent on the surface before warping and sizing. The main component of the wetting agent for low-dielectric glass fiber yarn is hydroxypropyl starch, which has weak anionic properties and is mainly bonded to the glass fiber surface through hydrogen bonds. The wetting agent first forms a slurry layer on the surface of the glass fiber. In the weaving process, the slurry used for the glass fiber is actually coated on the wetting agent slurry layer on the surface of the glass fiber yarn. Therefore, by examining the contact angle of slurries with different formulations on the wetting agent film, its wetting and viscosity capabilities on the glass fiber yarn can be characterized.

[0092] In Table 2, the contact angles are the contact angles of different slurry formulations on the sizing film, which effectively evaluates the wetting and adhesion of the slurry to the glass fiber yarn. Figure 1 The following are the contact angle test results of different slurry formulations on the wetting agent film. See the test results in Table 2 and Figure 1With the increase of the proportion of starch complex in the slurry, the contact angle tends to increase gradually. This is consistent with the above analysis that the slurry is affected by the high molecular weight and viscosity of starch, and the branching structure of the main chain. The flow resistance gradually increases and the flow performance weakens, resulting in the weakening of the wetting and spreading performance of the glass fiber yarn on the surface of the wetting agent film. Therefore, the slurry suitable for low dielectric glass fiber yarn should have a smaller contact angle.

[0093] (3) Stability of slurry: The stability of slurry determines its use and storage cycle, and directly affects the large-scale continuous production effect of glass fiber electronic cloth and the stability of product quality, so it is also one of the important indicators; Specifically, the stability of slurry is characterized by the change in turbidity and phase separation of slurry after being stored at a constant temperature (such as sizing temperature) for a certain period of time; the slurry anti-settling test method is: take 50 ml of the prepared combined slurry under the slurry boiling conditions of Example 2, cool it to 60°C in a constant temperature water area, place it in a 50 ml stoppered colorimetric tube, and then keep it at 60°C. Starting from the standing time of 1 hour, take pictures every 1 hour to observe the slurry sedimentation and phase separation; the stability is mainly characterized by the slurry anti-settling and turbidity change; the slurry turbidity test method is: take 50 ml of the prepared combined slurry under the slurry boiling conditions of Example 2, cool it to 60°C in a constant temperature water area, place it in a 50 ml stoppered colorimetric tube, and then keep it at 60°C. Starting from the 1-hour standing time, the turbidity of the slurry was measured with a turbidimeter every 1 hour.

[0094] like Figure 2 The following are test graphs of turbidity change and anti-coagulation performance of different slurry formulations after static aging for 1 to 5 hours at 60°C. Figure 2 , the slurry formula with low starch complex content (Comparative Example 4 and Comparative Example 5) is prone to coagulation and has significant phase separation; as the starch complex content gradually increases, the slurry anti-aging property also gradually improves, indicating that the cationic modified starch complex can stabilize the slurry to a certain extent. The reason is that the cationic modified starch has a long side group and a strong steric hindrance, which can play a spatial isolation role between the macromolecules of starch and polyvinyl alcohol, preventing the aggregation of slurry particles and avoiding the occurrence of precipitation; however, as the proportion of starch complex in the slurry formula increases, the slurry anti-aging property also gradually increases, indicating that the cationic modified starch complex can stabilize the slurry to a certain extent. The turbidity of the slurry gradually increases with the addition of starch, especially when the starch ratio exceeds 45% (Comparative Examples 2 and 3), the turbidity of the slurry rises sharply. The reason is that, unlike PVA and PEG, which form a true macromolecular solution after dissolution, starch exists in the slurry in the form of aggregates composed of dissolved macromolecules, colloidal particles and micron-sized suspended particles after gelatinization. The increase in its ratio will increase the turbidity of the slurry. At the same time, because the positive charge carried by the cationic modified starch has a strong electrical neutralization effect with other components in the slurry when the ratio is too high, the slurry particles will be destabilized and precipitated, resulting in increased turbidity.

[0095] In summary, based on the comprehensive test results of the slurry in terms of surface tension, viscosity, wettability and stability, in the composite slurry of the present invention, the appropriate weight ratio of starch complex, partially hydrolyzed polyvinyl alcohol and polyethylene glycol is (1.4-1.6):1:1; the surface tension of the composite slurry at this ratio is 18.13 N / cm, and the viscosity is 9.5 mPa.s, both of which are at a relatively low level; at this time, the wetting angle of the slurry is 65.16°, which has good fluidity and permeability, as well as good permeability and wettability to glass fiber yarn, and if the proportion of starch complex continues to increase, the surface tension and viscosity of the slurry will increase significantly, and the slurry performance will deteriorate sharply; in addition, the stability of the slurry has been characterized, and it also shows the best slurry stability under this ratio.

[0096] (III) The performance influence of different component sizing formulas on thermal desizing effect:

[0097] Similar to conventional textile processing, after glass fiber electronic yarn is woven into glass fiber electronic fabric, it needs to be desized to ensure the subsequent processing. Since glass fiber fabric is an inorganic non-metallic material, the thermal desizing method is generally used, that is, the sizing, impregnation, additives and other organic substances on the surface of the fabric and yarn are removed by simmering. In the thermal desizing process, the simmering time is the key factor, because if the time is insufficient, the organic content of the slurry on the surface of the fabric will remain too much, and if the time is too long, the mechanical properties of the glass fiber yarn and fabric in the fabric will decrease. Therefore, the shorter the thermal desizing time required for the slurry, the better the performance of the slurry.

[0098] In this test, the same low dielectric glass yarn was subjected to the same sizing treatment using the sizing agent of Example 2, and after forming a fabric, the same method was used for thermal desizing treatment, and the residual mass rate and breaking strength of the low dielectric glass yarn after different sintering time were tested. Among them, the thermal desizing treatment method is: take 5g of sizing yarn, sinter at 410℃ in a muffle furnace for different time (2h~14h); the mechanical properties of sizing yarn are to test the tensile strength and breaking elongation of sizing yarn using a single yarn strength machine, and investigate the influence of different sizing formulas and different sintering time on the mechanical properties of two glass fiber electronic yarns. The residual strength of the sizing yarn after rubbing 100 times with a 25g weight in a fiber cohesion tester is used to characterize the flexibility of the electronic yarn; specifically, the mass loss rate of the glass fiber yarn is expressed as: (mass of the glass fiber yarn before simmering - mass of the glass fiber yarn after simmering) / mass of the glass fiber yarn before simmering × 100%, the mass residual rate of the glass fiber yarn = 100% - mass loss rate of the glass fiber yarn; the simmering conditions are set as: increasing from room temperature to 410°C at a rate of 10°C / min, and taking the fabric for performance testing after different simmering times at 410°C; the specific test results are shown in Table 3 below.

[0099] Table 3:

[0100]

[0101] From the test results of Table 3, it can be seen that the mass retention rate of the low dielectric glass fiber yarn of the formula of Example 2 changes significantly within the first 2 hours, and then gradually decreases with the extension of the simmering time. The change trend slows down after 4 hours, and basically stabilizes after 8 hours; it can be seen that the extension of the thermal desizing time can further reduce the yarn mechanical strength of the low dielectric glass fiber yarn fabric; in contrast, the mass retention rate of the low dielectric glass fiber yarn of Comparative Example 5 decreases significantly slower than that of Example 2. This is because the proportion of starch complex in the slurry of Comparative Example 5 is low, the corresponding proportion of polyvinyl alcohol is high, and polyvinyl alcohol has a higher heat resistance than starch, so that under the same simmering conditions, the decomposition speed of the slurry layer on the surface of the glass fiber yarn is slower, and more than 10 hours are required for the yarn quality to stabilize. Therefore, the surface slurry of the yarn of Comparative Example 5 is completely removed, and a longer thermal desizing time is required, and the extension of this time will inevitably cause the sizing quality to further decrease, which is unfavorable for maintaining the mechanical properties of the yarn. Therefore, a better starch content is conducive to shortening the simmering time, retaining the mechanical strength of the yarn to a greater extent, and reducing the amount of organic matter residue on the surface of the yarn, which is conducive to subsequent processing.

[0102] In the sizing process of glass fiber yarn, the sizing material plays two roles: penetration and coating. Figure 3 Part (a) shows an electron microscope image of a yarn initially coated with the slurry of Example 2 on a low dielectric glass fiber yarn, as shown in FIG. Figure 3 Part (b) shows the electron microscope image of the low dielectric glass fiber yarn after thermal desizing after simmering for 12 hours. Figure 3 As can be seen from the two figures in , after the low-dielectric glass fiber yarn is sized on the small single yarn sizing test machine, the sizing agent is more evenly coated on the surface of the yarn body of the low-dielectric glass fiber yarn, and forms a connected protective layer in the form of a sizing film, so that during the weaving process, the sizing yarn is effectively protected from the wear of the heald, reed and other machine parts and the adjacent yarns; at the same time, it can be observed in the figure that the fibers are closely adhered to each other through the sizing bonding layer to form a yarn body with good bundling, which further enhances the encapsulation force between the glass fibers in the electronic yarn, thereby enhancing the ability of the yarn to resist external mechanical effects; and Figure 3 In part (b), after sintering at 410°C for 12 h, the yarn surface tends to be smooth and there are fewer combustible residues (granular protrusions on the yarn surface), indicating that most of the combustible organic matter on the fiber surface has been decomposed, which is conducive to the smooth progress of the finishing process.

[0103] The slurries of Examples 1-4 and Comparative Examples 2-5 were subjected to heat treatment performance tests; wherein,

[0104] The thermogravimetric analysis conditions were set as follows: increasing the temperature from room temperature to 410°C at a rate of 10°C / min and treating at 410°C for 2 h; the calculation formula for the residual mass of the plasma membrane was: (mass of the plasma membrane before thermogravimetric analysis - mass of the plasma membrane after thermogravimetric analysis) / mass of the plasma membrane after thermogravimetric analysis × 100%;

[0105] The sintering conditions were set as follows: increasing the temperature from room temperature to 410°C at a rate of 10°C / min, and sintering at 410°C for 6 hours; the calculation formula for the mass loss of the sizing yarn was: (mass of the glass fiber yarn before sintering - mass of the glass fiber yarn after sintering) / mass of the glass fiber yarn before sintering × 100%.

[0106] The specific test results are shown in Table 4 below.

[0107] Table 4:

[0108]

[0109] From the test results in Table 4, it can be seen that in the thermogravimetric analysis, as the proportion of starch complex in the slurry decreases, the residual mass of the size film basically shows a trend of gradual increase; while as the proportion of starch complex in the slurry decreases, the mass loss of the sizing yarn basically shows a trend of gradual decrease, which indicates that as the proportion of starch increases, the slurry on the surface of the glass fiber yarn is more easily thermally degraded, which is beneficial to reducing the organic residue on the surface of the yarn and improving the mechanical properties and surface electrical properties of the yarn and fabric; at the same time, referring to the above test results in Table 4 and the test results shown in Table 2, in order to avoid the problem of relative increase in slurry viscosity and surface tension, which will cause the yarn permeability to weaken, the proportion of starch complex in the slurry is preferably 40% to 45%. Within this ratio range, the slurry has good slurry properties, including: suitable viscosity, low surface tension, good yarn forming performance, high yarn mechanical strength, good thermal decomposition performance of the size film, while ensuring the quality of the sizing yarn, reducing the thermal decomposition time as much as possible, and preserving the mechanical strength of the electronic yarn to the greatest extent.

[0110] To sum up, the cationic-oxidized esterified starch composite slurry for low dielectric glass fiber electronic yarn of the present application is prepared by compounding cationic modified starch with oxidized esterified modified starch to form a starch composite, and compounding it with polyvinyl alcohol and polyethylene glycol in a specific proportion. It can replace traditional chemical slurry to the greatest extent, not only ensuring the quality of sizing yarn while reducing the sizing cost, but also reducing the combustible content on the surface of low dielectric glass fiber electronic yarn, shortening the smoldering time, and retaining the mechanical strength of the fabric to the greatest extent. This is also the third innovation of the present invention.

Claims

1. A starch-based composite slurry for low-dielectric glass fiber electronic yarn, characterized in that: It is composed of starch complex, partially alcoholyzed polyvinyl alcohol, polyethylene glycol and water; the starch complex is composed of equal weights of cationic composite modified starch and oxidized esterified double modified starch; the weight ratio of starch complex, partially alcoholyzed polyvinyl alcohol and polyethylene glycol is (1.4-1.6):1:1; wherein, The chemical structure of cationic modified starch is: Wherein, n is 600~800; The chemical structure of oxidatively esterified double-modified starch is: Wherein, o is 300~400, p is 300~400; The partially alcoholyzed polyvinyl alcohol is polyvinyl alcohol with an alcoholysis degree of 87% to 89%; the polyethylene glycol is polyethylene glycol-4000.

2. The starch-based composite slurry for low-dielectric glass fiber electronic yarn according to claim 1, characterized in that: Cationic modified starch is prepared by modifying natural starch by aqueous phase nucleophilic substitution method using cationic epoxide as a modifier. The chemical structure of cationic modified starch is:

3. The starch-based composite slurry for low-dielectric glass fiber electronic yarn according to claim 1, characterized in that: Oxidative esterified double-modified starch is prepared by modifying natural starch through water phase nucleophilic substitution method with hydrogen peroxide as oxidant and acetic anhydride as esterifying agent.

4. The starch-based composite slurry for low dielectric glass fiber electronic yarn according to claim 1, characterized in that: The amount of water used is such that the solid content of the cationic modified starch, the oxidized esterified double modified starch, the partially alcoholyzed polyvinyl alcohol and the polyethylene glycol is 9.5wt.% to 10.5wt.%.

5. A method for preparing a starch-based composite slurry for low-dielectric glass fiber electronic yarn as described in any one of claims 1 to 4, the steps of which are: taking 57.5% to 62.5% of the total weight of water; adding polyethylene glycol to the water under stirring and stirring to dissolve; then adding partially hydrolyzed polyvinyl alcohol, cationic modified starch and oxidized esterified double modified starch in sequence, and after the addition is completed, continuing to stir for 5 minutes to obtain a mixed solution; heating the mixed solution to 93.5°C to 96.5°C and keeping it warm for 30 minutes to ensure uniform gelatinization; finally, adding the remaining pure water to the gelatinized solution and cooling it to 60°C to obtain a composite slurry.

6. A sizing process using the starch-based composite sizing agent for low-dielectric glass fiber electronic yarn as claimed in claim 5, comprising the steps of: sizing the low-dielectric glass fiber electronic yarn with the composite sizing agent in a single yarn sizing machine; wherein: The sizing tank temperature is 58℃~62℃, the sizing speed is 48.5m / min~51.5m / min, the sizing force is 0.45KN~0.55KN, double dipping and double rolling, and the drying room temperature is 77℃~83℃.

Citation Information

Patent Citations

  • Method for synthesizing composite modified starch slurry

    CN102585021A

  • Preparation method for sulfonation modification type composite modified starch size

    CN105399846A

  • Dual etherified starch, preparing method, and application of dual etherified starch

    CN106749711A

  • Novel glass fiber slurry and preparation method thereof

    CN118420244A

  • Four element complex denatured starch sizing material and its preparation method and application

    CN1478794A

Cited By

  • Low-combustible-matter combined slurry for ultralow-dielectric-loss quartz glass fiber cloth and preparation method of low-combustible-matter combined slurry

    CN120864807A